Meta-Analysis of Discovery Learning Model in Physics Learning - Hanifah Roihana Labibah; Mukhayyarotin Niswati Rodliyatul Jauhariyah (Jurnal Ilmiah Pendidikan Fisika, 2021)
This study aims to analyze the effect of the Discovery Learning learning model on physics learning which is reviewed based on all verified articles, education level, research results or response variables, media used, and learning materials. The research method used is meta-analysis. The flow of the meta-analysis research is the first to determine the research topic, the second to determine the criteria for selecting the data, the third to search for the data, the fourth to classify the data information, and finally to analyze and conclude. The data collected is secondary data derived from previous research in the form of 22 scientific publication articles. The data analysis technique uses effect size values. The results of this meta-analysis obtained an average effect size value of 0.852. The application of Discovery Learning in learning physics has a big effect when applied at the high school level and can improve science process skills in students. Discovery Learning has a big influence on the kinetic theory of gases with rocky virtual lab learning media.